ANALISIS KOMPARATIF KINERJA KEUANGAN BERDASAKAN RASIO KEUANGAN PADA PT JASA MARGA (PERSERO) TBK DAN PT CITRA MARGA NUSAPHALA PERSADA TBK - Alawiyah, Nur Rahmi; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze and compare the financial performance of PT Jasa Marga (Persero) Tbk and PT Citra Marga Nusaphala Persada Tbk based on financial ratios. The research method used is a comparative method with a quantitative approach. The data used are secondary data in the form of financial statements of both companies over a certain period. The analysis employs several financial ratios, including liquidity ratios, solvency ratios, activity ratios, and profitability ratios.The results show that there are differences in the financial performance of the two companies. PT Jasa Marga (Persero) Tbk tends to demonstrate better performance in terms of profitability and activity, while PT Citra Marga Nusaphala Persada Tbk shows advantages in certain liquidity aspects. These differences are influenced by operational strategies, capital structure, and asset management efficiency of each company.In conclusion, both companies have their own strengths and weaknesses in financial performance. Therefore, comprehensive financial ratio analysis is essential to provide a more accurate basis for decision-making for investors and management.